THE CHARACTERISTIC OF PHYSICO-CHEMICAL AND CONSUMER PREFERENCE OF MUSHROOM’S CHIPS DURING ROOM TEMPERATURE STORAGE - T.F. Djaafar; Siti Raharu; Murwati Murwati (Fakultas Pertanian, Universitas Janabadra, 2005)
The mushroom represent the horticulture commodity which high nutrient. In this time, in Yogyakarta have been developed of mushroom cultivation, especially in Pakem and Cangkringan Sub district, Sleman Regency. This research was aim to know the consumer preference and physic-chemical characteristic of mushroom’s chips during room temperature storage. This research was carried out in Post Harvest and Mechanical Laboratory, AIAT Yogyakarta. This research was done in two phase. The first phase done by making of mushroom’s chips using four kinds ingredient. The Random Device Complete was used as methodology research to choose the mushroom’s chips which liked consumer. As for flavor which is used as following : Treatment A ( 20 % garlic + 15 % salt to dry mushroom weight); Treatment B (20% garlic+15% salt + 0.4% jinten + 0.8% pepper to dry mushroom weight); Treatment C ( 20% garlic + 15% salt + 1.6% coriander to dry mushroom weight) and Treatment D (20% garlic + 15% salt + 40% onion + 1.6% coriander to dry mushroom weight). Sensory evaluation was examined with five hedonic scale method for color, texture, flavor, taste and for all liked to chosen the mushroom’s chips which liked by consumer. The second phase was done by making mushroom’s chips with the ingredient that liked by consumer and then were wrapped with aluminum foil and plastic bag and the were kept at room temperature during four weeks. The methodology research in this packaging and storage treatment was done by Random Device Complete with five repeated. The examination was carried out periodical for each week. During storage of mushroom’s chips was carried out of sensory evaluation and consumer acceptance with the hedonic scale method to color, texture, flavor, taste and entirety likely. Others, is also conducted by a examination periodical each week to moisture content, protein, fat, and peroxide number and also the characteristic of texture this case hardness mushroom’s chips with the Lloyd Instrument Unit. The result of this research indicate that the consumer prefer the mushroom’s chips which yielded with the gift of garlic and salt with the making expense equal to Rp. 8.515,- each 100 g of dry mushroom weight. During storage, protein content in mushroom’s chips that wrapped with two kind of package was constant, while the fat content was decrease and peroxide number was increase. But peroxide number increased in aluminum foil bag was smaller than in plastic bag. The crispy of mushroom’s chips in aluminum foil bag was 0.043 N/mm2. So the mushroom’s chips which wrapped with aluminum foil were defensible during storage.